Parents and Their Adopted Chinese Children: Adoption and Racial Microaggressions in Diverse Communities. Issue 1 (2nd January 2023) - Baden, Amanda L.; Zhang, Xian; Matthews, Jessica A. K; White, Ebony E.; Harrington, Elliotte S.; Kitchen, Andrew; Mazza, Jonathan; Pinderhughes, Ellen E.
Abstract: In this study using both qualitative and quantitative analysis, we coded the types and community prevalence of racial microaggressions (RMAs) and adoption microaggressions (AMAs) experienced and reported by White adoptive families with children adopted from China. Analyses examined differences in microaggressions reported by transracial adoptive families living in communities varying in racial-ethnic diversity. All families experienced RMAs and/or AMAs. Community diversity was only related to the number of RMAs experienced, and specific microaggressions were significantly related to diversity level. Parents' interpretation of microaggressions differed based on diversity level.